State of the Art in Research on Optimum Design, Reliability and Control of Renewable Energy Microgrids - Abdulkarim, Abubakar; Faruk, Nasir; Oloyode, A. O.; Olawoyin, Lukman A.; Popoola, Segun I.; Abdullateef, A. I.; Ibrahim, O.; Surajudeen-Bakinde, N. T.; Abdelkader, S. M.; Morrow, John D.; Adediran, Y. A.; Jibril, Y. (ELEKTRIKA- Journal of Electrical Engineering, 2018)
This paper has presented a comprehensive review in the area of microgrid from the design to implementation. The aim is to evaluate the current status, problems and research efforts toward realising functional microgrids in the power system. The expectations about microgrid are many; therefore the study is divided into three main sections. Recent advancements in the wind energy, solar energy and their future prediction are summarised. States of arts in optimum design of renewable energy microgrid are also investigated. In addition, critical literature review in the reliability analysis of microgrids consisting of renewable energy sources is also reported. Control of microgrids consisting renewable energy sources have been presented. Some examples of existing microgrids across the globe are critically reviewed. The work therefore recommends that energy planners and all stakeholders should consider environmental and regional difference in microgrids planning. Finally, future research areas and directions in these areas are highlighted.